2006
DOI: 10.1080/09553000600840922
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone effects on children's event-related oscillatory EEG during an auditory memory task

Abstract: The current findings suggest that EMF emitted by mobile phones has effects on brain oscillatory responses during cognitive processing in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 48 publications
0
48
0
Order By: Relevance
“…Conversely, whenever attention-demanding mental activity in subjects augments, neuronal activity increases in frontoparietal circuits and alpha power decreases''. Therefore, if alpha rhythm reflects a baseline cortical de-activation, then the increase of alpha power following MP EMF exposure, as observed by several authors [Reiser et al, 1995;Mann and Röschke, 1996;Borbely et al, 1999;Huber et al, 2000Huber et al, , 2002Krause et al, 2000bKrause et al, , 2006Croft et al, 2002;Cook et al, 2004;Curcio et al, 2005], points to a reduced cortical activation as a direct consequence of EMF exposure. Nonetheless, such an effect may also be due to an experimental bias in reproducing an actual situation of resting wakefulness, where the subject is supposed not to think or do anything.…”
Section: Discussion and Perspectivesmentioning
confidence: 74%
See 2 more Smart Citations
“…Conversely, whenever attention-demanding mental activity in subjects augments, neuronal activity increases in frontoparietal circuits and alpha power decreases''. Therefore, if alpha rhythm reflects a baseline cortical de-activation, then the increase of alpha power following MP EMF exposure, as observed by several authors [Reiser et al, 1995;Mann and Röschke, 1996;Borbely et al, 1999;Huber et al, 2000Huber et al, , 2002Krause et al, 2000bKrause et al, , 2006Croft et al, 2002;Cook et al, 2004;Curcio et al, 2005], points to a reduced cortical activation as a direct consequence of EMF exposure. Nonetheless, such an effect may also be due to an experimental bias in reproducing an actual situation of resting wakefulness, where the subject is supposed not to think or do anything.…”
Section: Discussion and Perspectivesmentioning
confidence: 74%
“…This study was recently repeated [Krause et al, 2004] with some methodological improvements (double-blind paradigm and left-side exposure), but no significant effect on oscillatory activity was reported. On the other hand, the same group [Krause et al, 2006] in a recent double-blind randomized and counterbalanced study on children (6 boys and 9 girls), reported that EMFs increase ERD/ERS differences during both encoding and recognition. In particular, wavelet signal analysis showed the generalization of a (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), an attenuation in the normal decrement over time of theta activity (4-8 Hz band), and an increase in gamma response (30-45 Hz band) over the midline frontal and lateral posterior sites.…”
Section: Effects Of Gsm-like Signals On Evoked Cerebral Activitymentioning
confidence: 89%
See 1 more Smart Citation
“…In terms of EEG measures of neural processes relating to audition, there is again no consistency. For example, three studies reported MP-related changes in event-related spectral power, but these were in different directions and frequencies (increase in 18.75Hz to 31.25Hz, Eulitz et al, 1998;decrease in 1-4Hz and increase in 8-12Hz, Croft et al, 2002; changes in 4-8Hz and 15Hz, Krause et al, 2006). Similarly, although there was consistency in event-related potential (ERP) research in that reduced N1 amplitude and latency was found by both Hamblin et al (2004) and Maby et al (2004), Hamblin et al (2006) were not able to replicate those 3 results with a stronger research design that had the added benefit of double-blinding, and this lack of effect was replicated by Kleinlogel et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies indicated that EMF caused a reduction in the voltage of slow potentials. However, a more detailed analysis of the results and their verification in further experiments did not confirm the earlier observations [12][13][14]. Considering the limitations of the EEG method, in our current work we decided to use determinations of P300 wave to assess EMF effect on auditory cortex ERPs.…”
Section: Discussionmentioning
confidence: 99%